Beyond Financial Constraints: Economic Precarity, Psychological Safety, and the ‘Marriage Postponement’ Phenomenon—A Cox Proportional Hazards Analysis of Gen Z’s Life Transitions in Urban Indonesia - Hanifah Yasin; Henry Peter Paul; Harun Urrashid; Amir Serikova (HM Publisher, 2025)
Indonesia is witnessing a significant demographic shift where Gen Z increasingly delays marriage, a departure from traditional norms. This study investigates how economic precarity—characterized by job instability and rising living costs—impacts the timing of marital transitions. Utilizing a longitudinal dataset of 1,500 urban-dwelling Gen Z individuals (ages 18–28) in Jakarta, Surabaya, and Bandung, this research employs Survival Analysis, specifically Kaplan-Meier and Cox Proportional Hazards models, to identify the hazard of marriage relative to economic indicators. The findings reveal that Gig Economy employment reduces the marriage hazard rate by 42 percent compared to formal sector employment. High debt-to-income ratios and housing unaffordability are identified as primary predictors of postponement. Interestingly, female Gen Zers with high educational attainment show a higher propensity for postponement, citing the double burden of domestic and professional roles. In conclusion, marriage in urban Indonesia is no longer just a social milestone but a calculated economic risk. Policy interventions should focus on housing stability and formalizing the informal labor market to support demographic sustainability.